Identifying and intervening to stop school bullying: the role of school resource officers. Issue 3 (28th July 2021) - Paez, Gabriel R.; Colvin, Roddrick
Abstract : Purpose: The purpose of this study is to explore school resource officers (SROs) and their role in preventing, detecting and intervening in bullying incidents. Design/methodology/approach: Using data from 214 survey respondents, the present study attempted to identify the personal and situational characteristics that help to understand when SROs are likely to identify and intervene in bullying incidents. Findings: Taking a multivariate logistic regression approach, the results show that SROs – regardless of race, age, gender and education – who can identify instances of bullying are more likely to intervene to stop it. Research limitations/implications: The implications of improved training for SROs are discussed, as are ways to enhance the integration of SROs into schools' overall anti-bullying efforts. Originality/value: Bullying and violence in schools have been a growing concern for school districts and SROs are being increasingly seen as critical components of anti-bullying programs.